Effects of The Geometer’s Sketchpad on Algebraic Reasoning Among Junior Private High School Students - Hwa Li Li; Hutkemri Zulnaidi (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2019)
Previous studies reported the student’s difficulties in algebraic reasoning for solving problems involving quadratic equations. Mostly full to the agreement of understanding and solving quadratic equations is the conceptual challenge in subject mathematics. Integrating technology in the national school curriculum enhances the teaching and learning development throughout the science, engineering and mathematics in the facets of multidiscipline skills and reasoning in context. A quasi-experiment was conducted to determine the effects of Geometer’s Sketchpad (GSP)-based instruction through using Geometer’s Sketchpad on the algebraic reasoning abilities of Junior Two students. The experimental study was conducted on 60 Junior Two students, who were equally divided into experimental (30 students) and control groups (30 students). The data were collected through algebraic reasoning abilities test. Data were analysed using ANATES 4 and SPSS 25.0. Inferential statistics including the independent sample t-test was used in analyzing the quantitative data obtained. Significant differences were found in the algebraic reasoning abilities of students in relation to quadratic problem solving according to their group type. GSP-based instruction helped students develop their algebraic reasoning abilities in the instructional intervention and provided insights for mathematics educators into utilising the software. Moreover, the effect of the GSP-based instruction enhanced the algebraic reasoning abilities of students without influence of prior knowledge.